Hepatitis B Virus Reactivation: Risk Factors and Current Management Strategies. Issue 12 (3rd November 2019) - Smalls, Danielle J.; Kiger, Reagan E.; Norris, LeAnn B.; Bennett, Charles L.; Love, Bryan L.
Abstract : Hepatitis B virus (HBV) is a global disease with significant morbidity and mortality. Worldwide, ~257 million people are chronically infected with HBV, defined as having a positive hepatitis B surface antigen, but millions more have prior HBV exposure indicated by positive hepatitis B core antibody. Reactivation of hepatitis B implies a sudden increase in viral replication in a patient with chronic HBV infection or prior HBV exposure. Hepatitis B virus reactivation (HBVr) can occur spontaneously, but it is more commonly triggered by immunosuppressive therapies for cancer, immunologic diseases, or transplantation. Elimination of hepatitis C virus (HCV) in HBV‐HCV coinfected individuals treated with direct‐acting antivirals (DAAs) has also been identified as an important cause of HBVr. Hepatitis B virus reactivation is an underappreciated but important complication of common medical therapies that can delay treatment or result in clinical episodes of hepatitis, hepatic failure, or death. In this review, factors associated with HBVr, particularly medication‐related risks, are explored. We review data involving rituximab and ofatumumab, doxorubicin, corticosteroids, tumor necrosis factor antagonists, tyrosine kinases, bortezomib, hematologic stem cell transplantation, and DAAs for HCV treatment. In addition, we discuss screening strategies, choice of antiviral prophylaxis, and the optimal duration of therapy for HBVr. With additional awareness, screening, and appropriate antiviral therapy, it is expected that most cases of HBVr can be prevented.